Efeitos de um protocolo de intervenção de acupuntura sobre sintomas psicológicos qualidade do sono e imunossenescência em idosos - Zuppa, Carina (2014)
Introduction: Acupuncture is an Oriental therapy that has shown in several studies to be beneficial in treating various conditions. Several studies have shown acupuncture as a good treatment option for stress, depression as well as for improving sleep, however, few studies have a good design and robust control groups. Objective: the present work is to analyze the effect of acupuncture on stress, depression and sleep quality, as well as over the immune system. Methods: forty-eight elderly residents in the community took place in this single blind, placebo-controlled trial, randomized into two groups (n = 24 real acupuncture and control n = 24) placebo controlled. The intervention consisted of sessions held twice a week for five weeks thirty minutes long. The intervention consisted of ten (twice a week) true acupuncture sessions (n=24) or placebo (n=24). Acupuncture points involved were SP6 (Sanyityiao), LI4 (Hegu), ST36 (Zusanli), LR3 (Taichong), PC6 (Neiguan) and EX - NH3 (Yintang). Placebo group also received needle which were inserted into surface sites far from true acupuncture points. Sleep quality was assessed by questionnaire PSQI (Pittsburgh Sleep Quality Index), stress and depression were assessed through interviews where specific clinical questionnaires (Beck Depression Scale and BDI - II) were applied. Peripheral blood was collected and lymphocytes were isolated from peripheral blood mononuclear cells (PBMCs) and immunophenotyped by flow cytometry for several lymphocytes subtypes as B cells, activated T cells, regulatory T cells (REG), natural killer cells (NK) and CD28 - associated T cell senescence. Measurements were conducted before the beginning and at the very end of treatment. The groups were homogeneous at baseline. Results: acupuncture is highly effective for improving quality of sleep (-53.23 %, p < 0.01) depression (-48.41 %, p < 0.01) and stress (-25.46 %, p < 0 01). However, no effect on immune system could be observed. Conclusion: Acupuncture was effective in improving sleep quality and decreased stress and depression scores in the elderly. Further studies are necessary to investigate the impact of acupuncture on immunity.